2006
DOI: 10.1523/jneurosci.3524-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neural-Specific Inactivation of ShcA Results in Increased Embryonic Neural Progenitor Apoptosis and Microencephaly

Abstract: Brain size is precisely regulated during development and involves coordination of neural progenitor cell proliferation, differentiation, and survival. The adapter protein ShcA transmits signals from receptor tyrosine kinases via MAPK (mitogen-activated protein kinase)/ ERK (extracellular signal-regulated kinase) and PI3K (phosphatidylinositol 3-kinase)/Akt signaling pathways. In the CNS, ShcA expression is high during embryonic development but diminishes as cells differentiate and switches to ShcB/Sck/Sli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…5 In agreement with this time-restricted expression, the IL-9/IL-9R signaling pathway significantly prevented neuronal PCD both in vivo and in vitro. This antiapoptotic effect seemed to similarly affect different cortical areas (motor, somatosensory and visual cortices) but, within each cortical area, to preferentially affect the superficial layers as supported by anticleaved caspase-3 immunostaining and in situ hybridization for IL-9R mRNA.…”
Section: 14supporting
confidence: 55%
See 1 more Smart Citation
“…5 In agreement with this time-restricted expression, the IL-9/IL-9R signaling pathway significantly prevented neuronal PCD both in vivo and in vitro. This antiapoptotic effect seemed to similarly affect different cortical areas (motor, somatosensory and visual cortices) but, within each cortical area, to preferentially affect the superficial layers as supported by anticleaved caspase-3 immunostaining and in situ hybridization for IL-9R mRNA.…”
Section: 14supporting
confidence: 55%
“…[1][2][3][4] Alteration of developmental cell death can be associated with the etiology of several human nervous system abnormalities including hydrocephaly and microcephaly. 1,[5][6][7] The mechanisms of PCD are remarkably conserved among species and the molecular machinery relies on the mitochondrial pathways of intracellular signal transduction. 8,9 For example, null mutations of caspase-3 or caspase-9 in some mouse strains cause an enlarged forebrain due to the lack of normal neural progenitor apoptosis during development.…”
mentioning
confidence: 99%
“…11 Interestingly, mice with a conditional deletion of Shc in specific organs such as skeletal muscle, 11 thymocytes, 14 or brain 12 live to adulthood, exhibiting defects only in the function of the tissue in which Shc was removed. Similarly, we now show that endothelial Shc expression is not required for embryonic development, but is required postnatally for angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed gene-targeting work has shown that the expression of the PTB domain of Shc specifically in cardiomyocytes is critical for midgestational heart development and embryonic life. 11 Conditional knockout strategies have shown that Shc is also important for the proper development/function of other organs such as skeletal muscle, 11 brain, 12 cardiomyocytes, 13 and thymocytes, 14 because tissue-specific deletion of Shc resulted in living but underdeveloped mice. To address the role of Shc in angiogenesis in vivo, we studied loss of Shc function using morpholino (MO) antisense technology in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…The CNS specific intronic enhancer element has been widely employed to drive reporter genes or to target transgene expression to neural stem cells (Lardelli et al, 1996;Panchision et al, 2001;Magdaleno et al, 2002;McFarland et al, 2006;Mills et al, 2006;Walker et al, 2010). Expression of the tetracycline reverse transactivator (rtTA) and cells expressing the nestin transgene was examined by X-gal staining ( Fig.…”
Section: Noggin Can Be Inducibly Expressed In Nestin Positive Cells Omentioning
confidence: 99%